Distinct macrophage populations and phenotypes associated with IL-4 mediated immunomodulation at the host implant interface. (18th September 2020) - Hachim, Daniel; LoPresti, Samuel T.; Rege, Rahul D.; Umeda, Yuta; Iftikhar, Aimon; Nolfi, Alexis L.; Skillen, Clint D.; Brown, Bryan N.
Abstract : Macrophage populations and gene expression of the host response were studied under the effects of IL-4 released from eluting implants. Abstract : The host macrophage response to implants has shown to be affected by tissue location and physio-pathological conditions of the patient. Success in immunomodulatory strategies is thus predicated on the proper understanding of the macrophage populations participating on each one of these contexts. The present study uses an in vivo implantation model to analyze how immunomodulation via an IL-4 eluting implant affects distinct macrophage populations at the tissue-implant interface and how this may affect downstream regenerative processes. Populations identified as F4/80 +, CD68 + and CD11b + macrophages at the peri -implant space showed distinct susceptibility to polarize towards an M2-like phenotype under the effects of delivered IL-4. Also, the presence of the coating resulted in a significant reduction in F4/80 + macrophages, while other populations remained unchanged. These results suggests that the F4/80 + macrophage population may be predominant in the early stages of the host response at the surface of these implants, in contrast to CD11b + macrophage populations which were either fewer in number or located more distant from the implant surface. Gene expression assays showed increased proteolytic activity and diminished matrix deposition as possible mechanisms explaining the decreased fibrotic capsule deposition and improved peri -implant tissue quality shown in previous studies using IL-4 eluting coatings. The pattern of M2-like gene expression promoted by IL-4 was correlated with glycosaminoglycan production within the site of implantation at early stages of the host response, suggesting a significant role in this response. These findings demonstrate that immunomodulatory strategies can be utilized to design and implement targeted delivery for improving biomaterial performance.